A 10q21.3q22.2 microdeletion identified in a patient with severe developmental delay and multiple congenital anomalies including congenital heart defects. (17th May 2017) - Shimojima, Keiko; Okamoto, Nobuhiko; Yamamoto, Toshiyuki
Abstract: Interstitial deletions in the 10q21.3q22.2 chromosomal region are rare. A de novo microdeletion in this region was identified in a patient with severe developmental delay and multiple congenital anomalies, including congenital heart defects. The identified 10.4‐Mb deletion included 84 RefSeq genes. CTNNA3 and JMJD1C have been associated with cardiomyopathy and neurological impairments (autism and/or intellectual disability), respectively. Because there is no gene which shows one‐to‐one relation to clinical features observed in this patient, combinatory deletion of the genes in this region would be causative of the clinical features in this patient.